2017
DOI: 10.1515/sg-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Spring and autumn phenology of Bulgarian and German provenances of Common beech (Fagus sylvatica L.) under similar climatic conditions

Abstract: The ongoing climate change creates serious concerns about how tree species will behave under new environmental condi­tions. Common beech (Fagus sylvatica L.), a main and important tree species in Europe, will also be affected by the coming changes. One possibility to test the adaptability of this tree species is to perform provenance tests, transplanting trees from northern areas to warmer and drier places, and to investigate their behavior over a long period of time (transfer experiments). This work describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…The origin of beech populations is a major determinant of the timing of their leaf spring and leaf autumn phenology (Table 1), which confirms their genetic differentiation in the control of phenology (Chmura and Rozkowski 2002; Petkova et al 2017, Alberto et al 2013). This differentiation is often stronger for spring phenology than for autumn phenology (Vitasse et al 2009; Weih 2009; Firmat et al 2017; Petkova et al 2017), which is in agreement with what we found in our beech provenances (Fig. 3a & b).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The origin of beech populations is a major determinant of the timing of their leaf spring and leaf autumn phenology (Table 1), which confirms their genetic differentiation in the control of phenology (Chmura and Rozkowski 2002; Petkova et al 2017, Alberto et al 2013). This differentiation is often stronger for spring phenology than for autumn phenology (Vitasse et al 2009; Weih 2009; Firmat et al 2017; Petkova et al 2017), which is in agreement with what we found in our beech provenances (Fig. 3a & b).…”
Section: Discussionsupporting
confidence: 56%
“…Although the dates of spring and autumn leaf phenological stages varied between the two years of our study, the same response-patterns persisted in both years (Figs. 3 and S1), suggesting a consistent effect of environmental conditions on the trials (Weih 2009; Friedman et al 2011; Petkova et al 2017). Our results also revealed larger differences among populations for both BB and LS in the Slovakian trial than in the German one (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These trends include clines in bud burst defined by longitude, latitude and altitude in European beech provenances (e.g. Nørgård Nielsen et al, 2003;Robson et al, 2011;Gömöry and Paule 2011;Schüler et al, 2012;Petkova et al, 2017), with the southeastern ones demonstrating earlier bud burst (Ivankovic et al, 2011;Ballian et al, 2015). Provenance tests all over the continent describe a general trend of populations growing in warmer and less continental climates to have an earlier bud burst than populations from colder climates (Robson et al, 2011).…”
Section: Leaf Phenological Traitsmentioning
confidence: 99%
“…Several provenance tests exist in Europe for beech, under field or glasshouse conditions (e.g. von Wühlisch et al, 1995;Nielsen and Jørgensen 2003;Czajkowski and Bolte, 2006;Gömöry and Paule 2011;Liesebach 2012;Schüler et al, 2012;Kreyling et al, 2012, Thiel et al, 2014Harter et al, 2015;Dounavi et al, 2016;Petkova et al, 2017), providing important information for forest management and conservation of beech populations.…”
Section: Introductionmentioning
confidence: 99%